The behavioural mechanisms of voluntary cooperation in WEIRD and non-WEIRD societies - Till O. Weber; Benjamin Beranek; Simon Gächter; Fatima Lambarraa-Lehnhardt; Jonathan F. Schulz (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2021)
We provide a framework to uncover behavioural mechanisms driving potential cross-societal differences in voluntary cooperation. We deploy our framework in one-shot public goods experiments in the US and the UK, and in Morocco and Turkey. We find that cooperation is higher in the US and UK than in Morocco and Turkey. Our framework shows that this result is driven mostly by differences in beliefs rather than in cooperative preferences, or peer punishment, which are both similar in the four subject pools. Our results highlight the central role of beliefs in explaining differences in voluntary cooperation within and across societies.
Keywords: C9; H4; C7; D2; 330; voluntary cooperation; experiments; public goods; cross-societal differences; behavioural framework